Effect of Ultraviolet Light Irradiation Combined with Riboflavin on Different Bacterial Pathogens from Ocular Surface Infection. (12th October 2017) - Shen, Jing; Liang, Qingfeng; Su, Guanyu; Zhang, Yang; Wang, Zhiqun; Liang, Hong; Baudouin, Christophe; Labbé, Antoine
Abstract : In order to study Staphylococcus epidermis and Staphylococcus aureus in vitro viability after the exposure to ultraviolet (UV) light and riboflavin, twelve strains of Staphylococcus epidermis and twelve strains of Staphylococcus aureus were isolated from patients with bacterial keratitis. The growth situation of Staphylococcus epidermidis and Staphylococcus aureus under different experimental conditions was qualitatively observed. The number of colonies surviving bacteria was counted under different UV light power and different exposure time. The experiment showed that there was no inhibition effect on the growth of bacteria using riboflavin alone. In UV alone group and UV-riboflavin group, inhibition effect on the bacteria growth was found. The UV-riboflavin combination had better inhibition effect on bacteria than UV irradiation alone. The amount of bacteria in the UV-riboflavin group was decreased by 99.1%~99.5% and 54.8%~64.6% in the UV alone group, when the UV light power was 10.052 mW/cm 2 and the irradiation time was 30 min. Moreover, with the increase of the UV power or irradiation time, the survival rates of bacteria were rapidly reduced. Compared with Staphylococcus aureus, Staphylococcus epidermis was more easily to be killed under the action of UV light combined with riboflavin.